2017
DOI: 10.1002/adsc.201700615
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Allenamides and Structurally Related Compounds by a Gold‐Catalyzed Hydride Shift Process

Abstract: A new procedure for the synthesis of allenamides and structurally related compounds is reported. Under gold catalysis, a series of ynamides possessing a benzyloxy group at the propargylic position were efficiently converted into the corresponding allenamides following a 1,5 hydride shift process. The scope of the reaction was shown to be extremely broad allowing the formation of γ‐mono or γ‐disubstituted allenes possessing various functional groups. Notably, and in contrast to previously reported methods, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…Further synthetic elaboration of this regioselective process is highlighted by preparing cyclic silyl ethers and bicylclic ketones in a separate work [283] . While mentioning on hydride migration, Zhao and Gagosz disclosed the rearrangement of ynamides possessing −OBn group at the propargylic site into allenamides via Au(I)‐catalyzed regioselective 1,5‐hydride shift [284] . Wang et al .…”
Section: Miscellaneous Rearrangementsmentioning
confidence: 99%
“…Further synthetic elaboration of this regioselective process is highlighted by preparing cyclic silyl ethers and bicylclic ketones in a separate work [283] . While mentioning on hydride migration, Zhao and Gagosz disclosed the rearrangement of ynamides possessing −OBn group at the propargylic site into allenamides via Au(I)‐catalyzed regioselective 1,5‐hydride shift [284] . Wang et al .…”
Section: Miscellaneous Rearrangementsmentioning
confidence: 99%
“…In 2017, Zhao et al reported the synthesis of N -allenamides and pyrroles ( Scheme 4 ) [ 40 ]. Under gold 42 catalysis, N -alkynylpyrrole bearing a benzyloxy group at the propargylic position 40 was converted into the corresponding allenepyrrole 41 , expelling benzaldehyde 43 .…”
Section: Synthesis Of [12]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…In 2012, Rabasso published a [2,3]-sigmatropic rearrangement of N -alkynyl amides [118]. The following year, 2013, during their investigations into the selective reduction of amino-allenephosphonates, Rabasso expanded the scope of their [2,3]-sigmatropic rearrangement to include N -alkynyl indole (Scheme 75) [119]. The researchers found that compound 279 , underwent a [2,3]-rearrangement when treated with diethyl chlorophosphite, giving N -allenylphosphate 281 in a 78% yield.…”
Section: Reactions Of N-alkynyl Azolesmentioning
confidence: 99%